C Programming - Lee, Mark (Global Media, 2011)
The most popular Operating Systems right now are Microsoft Windows, Mac OS X, and /Linux. Each is written in C. Why? Because Operating Systems run directly on top of the hardware. There is no lower layer to mediate their requests. Originally, this OS software was written in the Assembly language, which results in very fast and efficient code. However, writing an OS in Assembly is a tedious process, and produces code that will only run on one CPU architecture, such as the Intel X86 or AMD64. Writing the OS in a higher level language, such as C, lets programmers re-target the OS to other architectures without re-writing the entire code.